Consistency of the orbital chronologies derived for Vostok and EPICA DC ice cores based on the dependence of ice air content on local insolation - V. A. Khomyakova; N. A. Tebenkova; V. Ya. Lipenkov; D. Raynaud (Лëд и снег, 2025)
Total air content (TAC) is a multiproxy property of polar ice, which is thought to contain evidence of past changes in local insolation, summer temperature, meteorological conditions, and the elevation of glaciersat the site of ice formation. By revisiting two equally accurate TAC records obtained at the Vostok and EPICA DC drilling sites, we attempt a careful assessment of the contributions of different natural components(orbital and nonorbital, global and local), and of experimental uncertainties to the total variance of the TAC data. We show that a major contribution (~74 % of the total variance) is made by the nonthermal variations of the closeoff porosity, which includes the local insolation signal (~44 %) and the nonorbital variations of the firn properties related to changes in weather conditions (~30 %). The insolation signal has been used to produce TACbased timescales for the EPICA DC and Vostok ice cores (Raynaud et al., 2007; Lipenkov et al., 2011). In this paper, in order to better estimate the uncertainties of this dating technique, we compare the individual TAC timescales obtained for the two ice cores in their overlap age interval (150–390 ka) assuming that the insolationrelated variations should be the same and synchronous at the two sites, which sit at similar latitudes. We prove that CWT analysis is the most reliable technique for tuning the experimental TAC records to their local summer insolation targets (ISI). It provides excellent reproducibility of the deduced TAC timescales (0.3±0.2 ka) and good synchronization of the records obtained from the different ice cores even though the scattering of the TAC data is large. Finally, using the same CWT technique we come to the construction of the coherent TACbased orbital timescales for Vostok and EDC ice cores. Comparison of the TAC timescales with the optimized chronologies AICC2012 and AICC2023 for the Vostok and EDC cores showed that their discrepancy, as a rule, does not exceed 2 ka, which is consistent with both the standard error of the TACbased dating method (±2.1 ka) and the standard errors of the AICC2012 (±1.9…4.8 ka) and AICC2023 (±0.8…2.6 ka) reference chronologies themselves. We show that the increase in the uncertainty of orbital dating can be related to the natural weakening of variations of local insolation in some periods of time. The decrease in amplitude of the ISI variations implies reduction of the insolation signal and increase of the noise/signal ratio in the air content record. We did not find high amplitude shortterm (millennial scale) nonorbital TAC variations that were synchronous in both the ice cores that were studied. On the other hand, some of these variations are well reproduced by measurements in the replicate ice cores drilled several tens of metres apart, which confirms their significance and link with changes in the local conditions of ice formation. Based on our study, we argue that applying a multicore and dualproxy (TAC and O2/N2) approach would be advantageous for comprehensive investigation of the uncertainties associated with the combined use of TAC and O2/N2 records for orbital dating of existing (Vostok, EDC, Dome Fuji) and future ice cores, including those which will be drilled in central Antarctica as part of the Oldest Ice projects.